2009
DOI: 10.1038/cdd.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Ordering of caspases in cells undergoing apoptosis by the intrinsic pathway

Abstract: Caspases are a family of aspartate-specific cysteine proteases responsible for the biochemical and morphological changes that occur during the execution phase of apoptosis. The hierarchical ordering of caspases has been clearly established using dATPactivated cell lysates to model the intrinsic pathway induced by initial mitochondrial perturbation. In this model, caspase-9, the apical caspase, directly processes and activates the effector caspases, caspase-3 and -7, and then active caspase-3 but not caspase-7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
156
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 47 publications
10
156
2
Order By: Relevance
“…After oligomerization within a DISC, procaspase-8 undergoes auto-cleavage, and then translocates into the cytosol as an activated dimer harboring the active pocket with the active site Cys-283 (40,41). Procaspase-8 was also reported to be cleaved by caspase-6 resulting in the formation of the active dimer, which process might function to form the positive feedback loop of caspase activation in induction of apoptosis (42,43). Our DE mutant does not retain the Asp residue in linker sequences where procaspase-8 is cleaved by caspase-8 itself and other caspases.…”
Section: Discussionmentioning
confidence: 99%
“…After oligomerization within a DISC, procaspase-8 undergoes auto-cleavage, and then translocates into the cytosol as an activated dimer harboring the active pocket with the active site Cys-283 (40,41). Procaspase-8 was also reported to be cleaved by caspase-6 resulting in the formation of the active dimer, which process might function to form the positive feedback loop of caspase activation in induction of apoptosis (42,43). Our DE mutant does not retain the Asp residue in linker sequences where procaspase-8 is cleaved by caspase-8 itself and other caspases.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-6 is believed to be an effector caspase that is activated downstream of caspase-3 and -7 in apoptosome-mediated apoptosis. 74 Apart from lamin A/C, few other specific substrates for caspase-6 have been described, calling into question to which extent this particular caspase actually participates in drug-induced apoptosis. 75 However, it has been suggested that caspase-6 cleavage of tau protein leads to neurofibrillary tangle formation during Alzheimer's disease pathogenesis.…”
Section: Caspases and Cancer M Olsson And B Zhivotovskymentioning
confidence: 99%
“…It has been reported that caspase-6 is activated only following activation of caspase-3 or caspase-7 and thus is not activated directly by an initiator caspase (Inoue et al 2009). Once active, caspase-6 can cleave initiator caspases-2 and -8, although the functional consequences of this cleavage (away from the initiator caspase activation platform) are unclear (Slee et al 1999;Inoue et al 2009). In contrast, other studies have showed that caspase-6 can be activated in the absence of caspase-3 or -7 activity (LeBlanc et al 1999;Allsopp et al 2000;Doostzadeh-Cizeron et al 2000).…”
Section: Caspase-6mentioning
confidence: 99%
“…Studies directed toward ordering of the caspase cascade and characterization of caspase substrates indicates that caspase-3 has both distinct and overlapping roles with caspase-7 and caspase-6 (Slee et al 1999;Lakhani et al 2006;Luthi and Martin 2007;Inoue et al 2009). Although it might appear that by the time apoptotic signals reach the point of caspase-3 activation, there is no salvaging the cell, caspase-3 is still regulated through a variety of posttranslational modifications.…”
Section: Caspase-3mentioning
confidence: 99%